PELATIHAN BERMAIN MUSIK ANGKLUNG UNTUK MENGEMBANGKAN KECERDASAN MUSIKAL ANAK USIA DINI DI PAUD ST. ANTONIUS DARI PADUA SINTANG - Yohanes Berkhmas Mulyadi; Suryameng Suryameng; Lorentina Lorentina; Agata Meli Somalinggi; Fransiska Yolanda; Priskyilla Priskyilla (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2025)
Every child has artistic potential within him. Art is also one aspect of a child's growth and development. Playing angklung music is an art as well as a world heritage that needs to be developed and trained from an early age so that children have a sense of art within themselves as well as to train concentration, patience, dan calm. This community service activity stems from the problem that children of PAUD St. Antonius from Padua sometimes play angklung musical instruments as they please, lack concentration and do not follow the instructions of the teacher. The purpose of community service is that children can learn how to play angklung music well and correctly, increase children's musical intelligence, train concentration, patience and calm as the benefits of playing angklung music. The method used is training and demonstration. The results of community service are that children can play angklung musical instruments happily and happily, musical intelligence begins to appear, children begin to concentrate and patiently follow the coach's instructions